Do Islamic Banking Indicators Affect Indonesia’s Economic Growth? Evidence from the VECM Model - Ariyani, Diyah; Sholihah, Erlinda; Utami, Cahyaning Budi; Dewi, Ivana Rosediana (MALIA: Journal of Islamic Banking and Finance, 2026)
Indonesia has experienced rapid growth in the Islamic banking sector, which is expected to contribute to national economic growth. This study examines the short-run and long-run relationships between Islamic banking performance and Indonesia’s economic growth proxied by Gross Domestic Product (GDP). Using quarterly data from Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) during 2012–2021, this study analyzes the effects of BOPO, ROA, ROE, financing, and Non-Performing Financing (NPF) on GDP through the Vector Error Correction Model (VECM). The results show that, in the long run, BOPO, ROE, and financing have a positive and significant effect on GDP, while NPF negatively affects economic growth. Meanwhile, ROA does not significantly influence GDP. The Granger causality test indicates a one-way causal relationship from GDP to financing and ROA. These findings confirm the important role of Islamic banking intermediation and financial performance in supporting economic growth in Indonesia. This study contributes to the literature by providing empirical evidence on the dynamic relationship between Islamic banking performance and economic growth in Indonesia using the VECM approach, covering both long-run equilibrium and short-run adjustment mechanisms. The findings also provide policy implications for strengthening Islamic banking performance and financing effectiveness to support sustainable economic development.